Good Agricultural Practices (GAP) to improve crop productivity in Rwanda - CGIAR Research Program on Rice (2021)
Improved varieties Buryohe and Yun yin 4, 21-d old seedlings at 20x20cm spacing, fertilizers and weed management were used. Through 200 demonstration plots 2000 rice farmers were trained through farmer field days. Overall, a yield gain of 1.5 to 3.3 t/ha was achieved with GAP component technologies.